Features of the chemical structure of urethane-containing polymers prepared on the base of rapeseed polyol - Boiko, V.V.; Kobrinа L.V.; Riabov, S.V.; Bortnitsky, V. I.; Vilensky, V. O.; Kercha, Yu.Yu. (Reports of the National Academy of Sciences of Ukraine, 2014)
Features of the chemical structure of urethane-containing polymers synthesized on the base of hydroxylated rapeseed oil (polyol) are examined. Analysis of the results shows that the macromolecular compounds obtained are segmented polyurethanes, whose thermal degradation occurs in two stages: hard blocks are destroyed at the first stage, while the polyol part (soft blocks) decomposes at the second stage, allowing one to identify the temperature area of the polymer destruction and, thus, its temperature region of operation.